ENHANCING GRADE 6 STUDENTS’ MASTERY OF THE PAST TENSE THROUGH AI-DRIVEN LEARNING - Faisal, Ahmad; Misrita, Misrita; Putri, Librina Tria (Program Studi Magister Pendidikan Bahasa Inggris, Program Pascasarjana, Universitas Palangka Raya, 2024)
The study investigated the effectiveness of AI-driven learning tools in enhancing Grade 6 students’ mastery of the past tense in English grammar. The research aimed to explore how artificial intelligence could be leveraged to facilitate personalized, adaptive learning experiences that promoted better retention and application of past tense rules. Employing a mixed-methods approach, the study combined quantitative measures of grammar proficiency with qualitative data from interviews and observations of student interactions with AI-based learning platforms. The participants, consisting of 60 Grade 6 students from a public school in an urban setting, engaged with an AI-powered application over a period of 8 weeks. Results indicated a significant improvement in students’ understanding and use of the past tense, with students reporting higher engagement and confidence in grammar tasks. The findings underscored the potential of AI tools to provide tailored learning experiences that catered to individual learning paces and styles. The study concluded that AI-driven learning environments could enhance grammar acquisition in elementary education, offering implications for future integration of technology in English language teaching.